Pengaruh Tingkat Keparahan Stenosis Mitral Terhadap Kadar Soluble Vascular Cell Adhesion Molecule-1 dan Soluble Intercellular Adhesion Molecule-1 - Pramono Sigit; Yoga Yuniadi; Indriwanto Sakidjan (The Indonesian Heart Association, 2014)
Background: Blood Soluble Vascular Cell Adhesion Molecule-1 (sVCAM-1) and Soluble Intercellular Adhesion Molecule-1 (sICAM-1) levels are increased in Mitral Stenosis (MS) patients, but whether this phenomenon is due to chronic rheumatic inflammation process or because of hemodynamic effect of mitral stenosis severity is not clear yet.Objective: This research aims to study the effect of mitral stenosis severity on blood sVCAM-1 and sICAM-1 levels.Method: This study is a cross sectional study. Research subjects were divided into 3 groups: control patients, pre BMV (Baloon Mitral Valvulotomy) group, and post BMV group (patients who have already undergone BMV for ? 1year). Blood sVCAM-1 and sICAM-1 were measured using quantitative sandwich immunoassay method in all groups, and echocardiographic study to evaluate MS severity (MVA (Mitral Valve Area), mMVG (mean Mitral Valve gradient), TVG (Tricuspid Valve Gradient), mPAP (mean Pulmonary Artery Pressure), and LAVI (Left Atrial Volume Index) were performed to pre BMV and post BMV group at the same day with the blood sample collections.Results: There were 23 normal subjects, 26 patients in pre BMV group, and 27 patients in post BMV group. The sVCAM-1 and sICAM-1 levels in patients with MS (pre BMV and post BMV group) were higher than normal control subjects (536,87 ± 251,68 ng/ml vs 536,87 ± 149,22 ng/ml; p<0,001 and 270,04 ± 111,67 ng/ml vs 216,43 ± 50,60 ng/ml; p=0,006), meanwhile there were no differences of sVCAM-1 and sICAM-1 levels between pre BMV and post BMV group (854,67 ± 227,26 ng/ml vs 809,22 ± 275,63 ng/ml; p=0,515 dan 279,98 ± 114,39 ng/ml vs 260,49 ± 110,38 ng/ml; p=0,539). There were also no significant correlation between mitral stenosis severity (MVA, mMVG, TVG, mPAP dan LAVI) with sVCAM-1 and sICAM-1 levels (p>0,05).Conclusion: There were no correlation between mitral stenosis severity with blood sVCAM-1 and sICAM-1 levels